STATISTICAL FARM REGISTER IN THE EU ACCEDING COUNTRIES - A CONCEPTUAL APPROACH - Crina Turtoi; Oguzhan Akyildirim; Plamen Petkov (Ekonomika Poljoprivrede (1979), 2012)
This paper is primarily dealing with the methodological concerns needed to be taken into consideration for the elaboration of the Statistical Farm Register. Core objectives of the Statistical Farm Register are identified and considerations with regard to the place of the Statistical Farm Register in the frame of the General System of Registers are presented. Basic terminology of the registers is spotted and methodological differences between the Statistical Farm Register and Administrative Farm Register were delineated. A general model of the Statistical Farm Register was elaborated and main updating principles were emphasised.